Implementation of cognitive development theory in play-based mathematics learning in kindergarten - Basuki, Latifah Rachmalia Eko; Hayati, Nur; Maryatun, Ika Budi (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background: This study is motivated by a gap in the literature concerning the absence of a comprehensive mapping of the integration of Piaget’s, Bruner’s, and Vygotsky’s cognitive development theories in play-based mathematics learning in early childhood education (ECE), particularly regarding the proportion of their implementation in classroom practices. Objective: This study aims to analyze the implementation patterns of the three cognitive development theories and to construct a new conceptual mapping regarding the balance between concrete exploration, representation, and social interaction in early childhood numeracy learning. Method: The study employed a systematic literature review of 20 scientific articles published between 2020 and 2025, complemented by field observations conducted in several kindergarten institutions in Bantul. Data were analyzed using thematic analysis techniques to identify dominant patterns and theoretical orientations. Result: The findings indicate that Vygotsky’s theory has the highest level of implementation (85%), followed by Piaget’s theory (80%) and Bruner’s theory (65%). This imbalance reflects a strong dominance of social-interactive approaches over representational approaches in play-based mathematics learning. Conclusion: In conclusion, early childhood numeracy instruction still requires stronger emphasis on representational aspects to ensure a more balanced and optimal integration of Piaget’s, Bruner’s, and Vygotsky’s cognitive development theories in play-based learning contexts.